2014
DOI: 10.1177/1933719113497267
|View full text |Cite
|
Sign up to set email alerts
|

Endometriosis Is Characterized by a Distinct Pattern of Histone 3 and Histone 4 Lysine Modifications

Abstract: Background: The histone modification patterns in endometriosis have not been fully characterized. This gap in knowledge results in a poor understanding of the epigenetic mechanisms (and potential therapeutic targets) at play. We aimed to (1) assess global acetylation status of histone 3 (H3) and histone 4 (H4), (2) measure levels of H3 and H4 lysine (K) acetylation and methylation, and (3) to identify histone acetylation patterns in promoter regions of candidate genes in tissues from patients and controls. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
64
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 86 publications
(135 reference statements)
8
64
0
Order By: Relevance
“…Our findings, along with increased H3K9me3, are in broad agreement with their results that higher methylation levels of H3K9 were detected in ectopic endometrium 38 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings, along with increased H3K9me3, are in broad agreement with their results that higher methylation levels of H3K9 were detected in ectopic endometrium 38 .…”
Section: Discussionsupporting
confidence: 93%
“…In addition, our findings are in broad agreement with high levels of H3K9me3, H3K27me3 and EZH2 in endometriotic cells 37 and with increased H3K9 and H3K27 methylation in endometriosis 38 .…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies in our laboratory showed that methylation levels of H3K27 were significantly higher in endometriotic lesions and endometrium from patients compared to endometrium of controls, using an immunoassay that does not distinguish among mono-, di-, and trimethylation. 17 The molecular roles of H3K27me1, H3K27me2, and H3K27me3 are known to be different; therefore, it is important to elucidate their respective levels in endometriosis tissues and also to take into account cellular compartment (stroma vs glands). In order to do so and to validate the results obtained with the immunoassay analysis, we analyzed the levels of H3K27me3 in human endometriotic and endometrial tissues on a TMA by IHC.…”
Section: à8mentioning
confidence: 99%
“…14,15 We have previously shown that endometriotic lesions are characterized by hypoacetylation of H3K9 and H3K16 and hypermethylation of H3K4, H3K9, and H3K27. 16,17 Based on these findings, we aimed to further study the relevance of H3K27me3 specifically in endometriosis.…”
Section: Introductionmentioning
confidence: 99%
“…Histone acetylation is generally associated with the activation of a gene expression. The analysis of the chromatin immunoprecipitation (ChIP) conducted by Monteiro et al 48 showed the hypoacetylation on the H3/H4 at the promoter regions of candidate genes was down regulated in endometriosis, namely HOXA10, ESR1, CDH1 and p21. 48 On the other hand, the steroidogenic factor 1 promoter gene underwent increased acetylation of H3 and H4 which correlated with the high expression of the gene.…”
Section: Epigenetic and Endometriosismentioning
confidence: 99%